The effect of pension wealth on employment - Sebastian Becker; Hermann Buslei; Johannes Geyer; Peter Haan (Institute for Fiscal Studies (IFS), 2023)
This study provides novel evidence about the pension wealth elasticity of employment. For the identification we exploit reform-induced variation of pension wealth that is related to the number of children but which does not affect the implicit tax rate of employment. We use a difference-in-differences estimator based on administrative data from the German pension insurance and find that, on average, the negative employment effect of pension wealth is significant and economically important. Heterogeneity analyses document a strong age pattern showing that the employment effects are driven by behavioral responses of women close to retirement. The age pattern is partly explained by the positive effect of pension wealth on disability pensions after the age of 60.
Keywords: H55; J13; J21; J26; 330; pension reform; pension wealth elasticity; female labour supply; retirement; differences in differences